Repairing corporate reputation damage in the South African chemical industry. - McLoughlin, Patrick John (My University, 2016)
Good corporate reputations can be a source of competitive advantage to any business but this reputation can be damaged in many ways. The ideas surrounding corporate reputation and how to repair a damaged reputation have been well studied in the business to consumer (B2C) markets but to date it has not been comprehensively studied in the business to business (B2B) markets. This research sets out to establish the key dimensions that a business must put into place to repair a damaged corporate reputation in B2B markets. The research also aims to establish process guidelines that a business can follow in order to repair a corporate reputation in the South African chemical industry. In order to achieve the stated aim of the research a qualitative methodology was used. The research data was conducted through semi-structured interviews with senior managers and executives of a business that had suffered severe reputational damage though a product failure. The information gathered from the interviews was analysed in order to determine what the respondents felt were the key dimensions and the process involved in repairing a corporate reputation in the industry. The results of the interviews showed that the key dimensions for repairing a corporate reputation are trust, authentic communication and innovation. Trust is an integral part of developing a corporate reputation as the stakeholders need to believe that they are going to derive their required value from that business whether they are customers, shareholders or employees. Trust is built over time through continually delivering on the performance and quality required by each of the stakeholder groups. Authentic communication provides the platform for the business to build relationships. Communication provides the information that the stakeholders require to make informed decisions about the business and therefore it must be authentic otherwise the trust from the stakeholder will be broken. Innovation is what sets a business apart from the crowd and thus it is important when rebuilding a reputation that an atmosphere allowing for innovation is created iii within the business. Innovation creates sustainability and is what stakeholders are looking for. In order for a business to rebuild its corporate reputation it must first identify the root cause of the reputational damage otherwise the strategies and solutions that are to be developed will not fully address the issue that is causing the reputational damage. The solutions and strategies must then be implemented and measured to ensure that they are addressing the cause of the reputational damage. In order for the reputation repair process to be successful the employees of the business must support the initiative and thus it is important for a business to ensure that as part of the strategy and internal marketing strategy is implemented concurrently with the reputational strategies. Measurements of the targets, as defined by the strategy, are imperative as this allows the business to evaluate the progress and make the required adjustments to the areas where the strategy is not being implemented according to plan. The process of reputational repair is not a once off process but rather a circular one similar to that of continuous improvement. Whilst a good corporate reputation will not ensure that the required opportunities can be exploited, but a poor reputation will prevent any of the opportunities from presenting themselves. It is extremely important that a business repairs its damaged reputation, and ensures that continued to monitoring and management ensuring the business remains sustainable. The recommendations of this research provide executive management in B2B markets with assistance with the key dimensions and process of repairing a corporate reputation.
Keywords: Corporate image -- South Africa. Business ethics -- South Africa. Public relations -- South Africa.